Left-handedness in cardiac surgery: who's right?. Issue 3 (3rd May 2020) - Cathenis, K.; Fleerakkers, J.; Willaert, W.; Ballaux, P.; Goossens, D.; Hamerlijnck, R.
Abstract: There is a paucity of literature describing potential issues related to lateral hand dominance in general and cardiac surgery. Nonetheless, during surgical training left-handedness can produce difficulties in the operating room that are not always understood or accepted by supervising right-handed surgeons. These problems can be easily overcome by practice and anticipation. This report aims to address laterality related issues in cardiac surgery and provide insight into techniques that may aid the left handed surgeon in a right handed dominated surgical environment. An ergonomically different approach, more convenient for the left-handed trainee, may facilitate learning, enhance confidence and increase surgeon satisfaction both for the trainer and trainee.